Efecto de la interacción de Ascochyta phaseolorum y Pseudomonas sp. sobre la morfología de los frutos de Sechium edule (Cucurbitaceae) - Vázquez, Nelly; Flores, Eugenia M.; Vargas, E. (Revista de Biología Tropical, 1986)
Ascochyta phaseolorum and Pseudomonas sp. were isolated from infected Sechium edule fruits collected in the Valley of Ujarrás, Costa Rica. Young and mature healthy fruits were inoculated with suspensions of fungus spores or bacteria and placed in humid chambers in the laboratory or in the greenhouse. Only the young fruits from the laboratory developed lesions. The lesions produced by the fungus are characterized by rupture and lysis of the epidermal cell walls, with posterior invasion of the mesocarp parenchyma and the vascular tissues. In general, tissue destruction is correlated to the size of the lesion; the infection may even cause rotting of the fruit. Bacterial lesions showed thickening of the walls of the surrounding cells, as well as cytoplasm granulation and inclusions of crystalline formations. Bacteria were not observed inside the wound. There was no difference between natural lesions in the fruits collected in the field and those induced in the laboratory.